The relationship of muscle oxygen saturation analyzer with other monitoring and quantification tools in a maximal incremental treadmill test - Osmani, F.; Lago-Fuentes, C.; Alemany-Iturriaga, J.; Barcala-Furelos, M. (Frontiers in Physiology, 2023)
Introduction: The study aims to explore whether NIRS derived data can be used to identify the second ventilatory threshold (VT2) during a maximal incremental treadmill test in non-professional runners and to determine if there is a correlation between SmO2 and other valid and reliable exercise performance assessment measures or parameters for maximal incremental test, such as lactate concentration (LT), RPE, HR, and running power (W).